(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article discusses the essence of ecological trails, presenting the definitions found in the professional literature. The main goals of the creation and the usage of ecological trails are discussed. The criteria for classifying ecological trails and the features of their creation are briefly presented. The article also highlights the educational significance of ecological trails, emphasizing their role in acquiring professional knowledge and enhancing students’ skills particularly for tourism department students. As a case study, the ecological trail at Yerevan Botanical Garden is analyzed to demonstrate its role in developing ecological competence of future tourism professionals. The article further proposes to organize an extracurricular lesson at Yerevan Botanical Garden aimed at developing students’ professional skills.